The Green Bonus: Carbon Reduction Effect of Sulfur Dioxide Emissions Trading Pilot Scheme - Zhao, Yang; Su, Shuling; Xing, Yafei; Yu, Lu; Cui, Shihao; Jiang, Decai; Xiao, Zumian (Frontiers in Environmental Science, 2022)
Market-oriented environmental policy has made an indelible contribution to promoting sustainable development in China. We consider the introduction of the Sulfur dioxide Emissions Trading Pilot Scheme (SETPS) as a quasi-natural experiment and adopt PSM-DID method to study the reduction effect of SETPS on corporate carbon emissions. We find that SETPS can effectively promote the carbon emission reduction of enterprises, which highlights the dual significance of market-based environmental regulation policies in the field of pollution reduction and carbon emission reduction. Considering the heterogeneity of enterprises, SETPS imposes a more significant effect on carbon emission reduction of enterprises with high energy consumption and high pollution. The mediation effect analysis indicates that the indirect reduction effects of SETPS on the carbon emission through the marketization process and the development of non-state-owned economy. In addition, results from the test of moderation effect suggest that both financing constraint and ownership are the moderation factors for SETPS to affect enterprise carbon emission reduction. The empirical results suggest that there exists such a green bonus: reduction effect of introducing the SETPS on firm level carbon emission and other pollutant discharges. It should be paid more attention by the authorities.